Kloos, Klusch, (K/C)Laas, Niels, Nietsch. Patronymic Formations from the First Name Nikolaus - Nistor, Adina-Lucia (Universitatea Transilvania Brasov, 2025)
In Medieval Germany, the name of Saint Nicholas of Myra was the second most frequently encountered first name after John. At least 1,000 German surnames were formed from the first name Nicholas. The abundance of these surnames is attributed to the various methods of surname formation, coupled with the fact that they were pronounced and written differently in all dialects. Among the patronymics undoubtedly derived from the first name Nicholas, the following ones stand out: Kloos < Niklos; Klusch < Niklos, Klos, Klus;(K/C)laas< Niklas; Ni(e)tsch(e) < the first syllable Ni(e)- from Nikolaus and the suffix -tsch(e);Niels, contracted from Nikolaus, bearing similarities to the first names Cornelius, Cornils. As for Laas, a surname of origin from the toponyms Laas, Laase, its presumed derivation from Nikolaos, namely Klaas, Klaus, cannot be proven due to a lack of linguistic evidence.
Keywords: Onomastics; Saint Nicholas of Myra; Patronymics: Kloos; Klusch; (K/C)laas; Niels; Nietsch; Toponymic Name Laas